The effects of Gross Domestic Product (GDP) and interest rate on the profitability of foreign commercial bank in Malaysia / Nazatul Shima Mohd Kasmani (Faculty of Business and Management, 2007)
Profit is essential of a competitive banking institution and the cheapest source of funds. It is necessary to see it as a necessary for successful banking in a period of growing competition on financial market. This is the reason why this study focus on the currently issue of bank profitability. The aim of this study is to identify the effect of Gross Domestic Product (GDP) and interest rate that influence foreign commercial bank's effectiveness to manage their asset and liabilities in order to achieve a profit. Profit the positive gain from an investment or business operation after subtracting for all expenses and also opposite of loss. To determine the effect of GDP and interest rate to the profitability of foreign commercial bank in Malaysia, this study using 7 foreign commercial bank in Malaysia. The time horizon is during 2001 to 2005 which is five years. The income statement and balance sheet are used to measure the profitability ratio of each bank. This study using Single and Multiple Regression Analysis to determine the Coefficient of Determination (R-Squared), T-Test and F-Test to predict the relationship of the variables and to examine the significant. There are some previous researchers have concluded that there are positive effects of GDP and interest rate to the bank's profitability. There are also some of them say oppositely which there is negative effect. This study also can be use by the investors as their guideline to know the effect of GDP and interest rate to the profitability of foreign commercial bank in Malaysia.